METHODS OF USING EDUCATIONAL TECHNOLOGIES IN TEACHING ENGINEERING SUBJECTS - Amanova Nozima Shavkatovna (European Science Publishing, 2025)
In general, the teaching profession is, by its very nature, highly individual. An important life role of each teacher is to be a master of his work, that is, to conduct advanced research in all aspects of science for the student. A teacher is described as very advanced, knowledgeable, or skillful in his work. The skill of a teacher is manifested in his work. First of all, a teacher must have a good grasp of the laws and mechanisms of the pedagogical process, including the generalized skills of a teacher. The technologies of his pedagogical techniques are of great importance.
Keywords: Educational technologies, highways, transport, technology, science, development, educational principles.